Impact of Infrastructure Availability to The Level of Slum Area in Banyumanik District - Astuti, Khristiana Dwi; Pangi, Pangi; Mahendra, Bayu Ika (Universitas Negeri Semarang, 2018)
Slum especially in big cities such as Semarang City occurred not only in the inner city but also spread tothe suburbs of Semarang City, one of them in Banyumanik District. Based on the Decree of Mayor of Semarang no.050/801/2014 about Determination of Slum Location at Semarang City, there are 6 (six) urban villages inBanyumanik District which have slum areas. Determination of the slum area is based on the Semarang City SlumInventory Study from 2010 to 2014. As a consequence, it is known that the main problem causing the development of slum settlement is related to the availability of environmental infrastructures : road network, sanitation, clean water, and drainage. This research was conducted to determine the slum level in the slum areas located inBanyumanik district based on the availability of environmental infrastructure. The analysis included descriptive analysis to explain the characteristics of slum settlements and the availability of existing environmental infrastructure, and scoring analysis to determine the impact of the availability of this infrastructure on the slum level.Based on the results of the analysis, shows that the slum settlements in RT 01 / RW IV of Jabungan have the highestslum level in Banyumanik district.